2022
DOI: 10.3390/cells11182827
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related NAFLD: The Use of Probiotics as a Supportive Therapeutic Intervention

Abstract: Human aging, a natural process characterized by structural and physiological changes, leads to alterations of homeostatic mechanisms, decline of biological functions, and subsequently, the organism becomes vulnerable to external stress or damage. In fact, the elderly population is prone to develop diseases due to deterioration of physiological and biological systems. With aging, the production of reactive oxygen species (ROS) increases, and this causes lipid, protein, and DNA damage, leading to cellular dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 221 publications
0
16
0
Order By: Relevance
“…Impairment of the functional barrier of the intestinal tract will lead to the entry of certain microorganisms into the circulation, which will then reach the liver and cause liver dysfunction, further affecting aging through the liver–gut axis [ 53 ]. At the same time, dysbiosis of the intestinal flora will lead to low-grade chronic inflammation, oxidative stress, and the production of various toxic metabolites; alterations in the composition and function of the intestinal flora are also associated with different liver diseases during aging [ 54 ]. Gut microbiota can promote gut health by regulating the metabolism and transport of trace elements (Se, Zn, Mn, Fe, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Impairment of the functional barrier of the intestinal tract will lead to the entry of certain microorganisms into the circulation, which will then reach the liver and cause liver dysfunction, further affecting aging through the liver–gut axis [ 53 ]. At the same time, dysbiosis of the intestinal flora will lead to low-grade chronic inflammation, oxidative stress, and the production of various toxic metabolites; alterations in the composition and function of the intestinal flora are also associated with different liver diseases during aging [ 54 ]. Gut microbiota can promote gut health by regulating the metabolism and transport of trace elements (Se, Zn, Mn, Fe, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, modifications in GM composition result in the endogenous production of ethanol, which consequently compromises the integrity of the intestinal barrier and incites ROS accumulation in hepatic stellate cells and Kupffer cells[ 37 ]. Studies have shown that probiotics can restore homeostasis in the GM and mitigate oxidative stress[ 67 ]. Specifically, members of the Lactobacillus genus have demonstrated the ability to modulate the expression of inflammatory cytokines, including but not limited to IL-6, IL-1β, IL-1α, IL-12, and interferon-γ, both in serum and colonic tissues.…”
Section: Potential Therapeutic Targets For Masldmentioning
confidence: 99%
“…Patients with autoimmune DED often experience damage to ocular surface tissues such as the cornea, conjunctival goblet cells, and lacrimal glands. This damage is frequently associated with alterations in gut microbial diversity and abundance (Bai et al, 2023), which can trigger systemic inflammation and contribute to a range of ocular disorders, including age-related macular degeneration, uveitis, diabetic retinopathy, and glaucoma (Bai et al, 2023;Campagnoli et al, 2023).…”
Section: Mechanism Of Action In Dry Eye Diseasementioning
confidence: 99%